PENGGUNAAN MEDIA GAMBAR UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA PELAJARAN IPS DI KELAS V SEKOLAH DASAR NEGERI 008 TELUK MEGA KECAMATAN TANAH PUTIH KABUPATEN ROKAN HILIR TAHUN AJARAN 2015/2016 - Yusmita '; Gusnardi '; RM. Riadi ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstrack: IPS education emphasizes providing direct experience and todevelop the competence that the students were able to explore and understand thenature of social processes around scientifically. In addition to quality education can notbe separated from the role of the teacher as facilitator and motivator. a teacher will beeasier to accomplish the desired objectives, if a teacher uses media or tools in theprocess of teaching and learning activities IPS